Peran Media Sosial Dalam Meningkatkan Minat Belajar Bahasa Arab di Kalangan Remaja - Zali, Muhammad; Ika Putri, Alifyah; Al Maghirah, Annisa; Nazwa Panjaitan, Aulia; Moestafidz, Chalieq; Rasyifa, Fayza; Hudzaifah Pohan, M. Harits; Balqis Tanjung, Nur Azizah Chairuna; Dila Seja T, Novia Syalsa; Nabila, Salma; Radya Ruslan, Shaiecka; Nurhaliza, Sindy; Nurhalijah, Sri (PT. Alahyan Publisher Sukabumi, 2025)
The development of the digital era has made social media an integral part of life, including in the field of education. Students not only use it to socialize, but also as a means of obtaining information and learning materials. In the context of Arabic language learning, social media such as YouTube, Instagram, and TikTok in Arabic present educational content that is interesting and easily accessible. This has the potential to improve students' understanding and language skills. Given the importance of motivation in the learning process, it is interesting to study how social media can play a role in encouraging students' enthusiasm in learning Arabic actively and continuously. This study aims to analyze the role of social media in increasing students' motivation in learning Arabic, as well as to identify the types of social media content that are considered most effective in arousing students' enthusiasm for learning. This research utilizes a literature study, by collecting and analyzing written sources, such as scientific journals and articles that discuss social media, learning motivation, and Arabic language learning. From the results of the study, the researcher tries to compile a complete picture of how social media can support the learning process of Arabic among university students. The results of the literature study show that social media plays a significant role in supporting Arabic language learning. Audio-visual content such as conversation videos and infographics can increase students' interest in learning. Two-way interaction on social media also encourages the active use of Arabic in informal contexts. The literature review concludes that social media is an effective alternative means to increase motivation to learn Arabic, by presenting a learning experience that is fun, flexible, and in accordance with the characteristics of the digital generation.